Painless Legs and Moving Toes as an Initial Presentation of Ischemic Stroke - Oh, Se Mi (The Korean Movement Disorder Society, 2009)
Painless legs and moving toes is an unusual syndrome, which has not previously been reported as an initial presentation of ischemic stroke. We encountered a 78-year-old woman who developed dysarthria and involuntary movement of her left toes that was clinically regarded as painless legs and moving toes. These symptoms appeared abruptly and simultaneously as the initial symptoms of stroke, and improved gradually with conservative management by intravenous hydration for a month. We suggest that, in our case, a cortical brain lesion caused by ischemic stroke might be associated with the development of painless legs and moving toes.